Copyright And Issues - Grace Effiong ETUKUDO; Luqman Ayanlola ATANDA; Etido Sunday UDOEDUOK (European Science Publishing, 2023)
This research work is all about copyright and issues. It talks about the right given to the originator, emanatory, founder of a particular intellectual work such as literature books like novels, textbooks on a specific subject, music producers, film makers and so on. Copyright is a law emanated to protect the right of original innovator form the reproduction of the work without any permission (piracy). Copyright does not cover the names of business, organizations or groups, pseudonyms of individuals, title of works, catchwords, catchphrases, mottoes, slogans or short advertising expression, listings of ingredients in recipes, labels, and formulas, though the directions can be copyrighted.
Keywords: copyright, issues, patent, intellectual property, law.